Gallic Acid Alleviates Gut Dysfunction and Boosts Immune and Antioxidant Activities in Puppies Under Environmental Stress Based on Microbiome–Metabolomics Analysis - Yang, Kang; Deng, Xiaolin; Jian, Shiyan; Zhang, Meiyu; Wen, Chaoyu; Xin, Zhongquan; Zhang, Limeng; Tong, Aorigeile; Ye, Shibin; Liao, Pinfeng; Xiao, Zaili; He, Shansong; et al. (Frontiers in Immunology, 2022)
Early-life exposure to environmental stress disrupts the gut barrier and leads to inflammatory responses and changes in gut microbiota composition. Gallic acid (GA), a natural plant polyphenol, has received significant interest for its antioxidant, anti-inflammatory, and antimicrobial properties that support the maintenance of intestinal health. To assess whether dietary supplementation of GA alleviates environmental stress, a total of 19 puppies were randomly allocated to the following three dietary treatments for 2 weeks: (1) basal diet (control, CON); (2) basal diet + transportation (TS); (3) basal diet with the addition of 500 mg/kg GA + transportation (TS+GA). After a week supplementation period, puppies in the TS and TS+GA groups were transported from a stressful environment to another livable location, and puppies in the CON group were then left in the stressful environment. Results indicated that GA markedly reduced the diarrhea rate in puppies throughout the trial period and caused a moderate decline of serum cortisol and HSP-70 levels after transportation. Also, GA alleviated the oxidative stress and inflammatory response caused by multiple environmental stressors. Meanwhile, puppies fed GA had a higher abundance of fecal Firmicutes, Lactobacillus, and lower Proteobacteria, Escherichia-Shigella, Clostridium_sensu_stricto_1 after transportation. As a result, The TS+GA group had the highest total short-chain fatty acids and acetic acid. Also, the fecal and serum metabolomics analysis revealed that GA markedly reversed the abnormalities of amino acid metabolism, lipid metabolism, carbohydrate metabolism, and nucleotides metabolism caused by stresses. Finally, Spearman correlation analysis was carried out to explore the comprehensive microbiota and metabolites relationships. Overall, dietary supplementation of GA alleviates oxidative stress and inflammatory response in stressed puppies by causing beneficial shifts on gut microbiota and metabolites that may support gut and host health.